Acardia anceps: the monster twin; twin reversed arterial perfusion (TRAP) syndrome - Khan, Shazia; Singh, Tina; Maiti, Gunadhar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Twin reversed arterial perfusion (TRAP) sequence is an extremely rare complication of monochorionic multi-foetal pregnancy, occurring once in 35,000 births. It is characterized by a malformed foetus without a heart being perfused by a structurally normal (pump) twin via an artery-to-artery anastomosis in a reverse direction. We report one such case where ultrasound imaging revealed monochorionic twin pregnancy with a viable, normal-appearing first twin and a structurally aberrant second twin with absent cardiac activity. The patient was monitored with two weekly ultrasonography and Doppler ultrasound examination to ascertain the well-being of the pump twin. She delivered successfully at term a normal live baby and an acardius anceps foetus. The perinatal mortality of the pump twin ranges from 35 to 55%; making it essential to diagnose the presence of a pump twin at an early gestational age through improved imaging techniques to plan effective intervention at appropriate time.